EVALUASI MUTU DODOL BERBASIS TEPUNG KETAN DAN BUAH PEDADA (Sonneratia Caseolaris) - Rudianto '; Noviar Harun; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to get the best treatment formulation and quality appropriate Indonesian National Standar (1996) of Fruit Dodol based on ratio level of Pedada’s flesh and Sticky Rice flour and find out the panelists’ favorite level toward the produced Dodol. This study used Complete Randomized Design (CRD) by 4 treatments and 4 replications: P1T1 (Pedada’s Flesh 20%:Sticky Rice Flour 80%), P2T2 (Pedada’s Flesh 30%: Sticky Rice Flour 70%), P3T3 (Pedada’s Flesh 40%: Sticky Rice Flour 60%), P4T4 (Pedada’s Flesh 50%: Sticky Rice Flour 50%). The results showed that the amount of Pedada’s Flesh and Sticky Rice Flour ratio has the real significant on the water content, crude fiber content, ash content, fat content, sucrose content, acidity, organoleptic assessment descriptive (color, aroma, flavour and texture) as well as evaluating the overall hedonic organoleptic. The best result of treatment formulation was P2T2 (30%:70%) with water content 15.70%, crude fiber content 3.98%, ash content 0.57%, fat content 4.60%, sucrose content46.30%, acidity 6.10, slightly brown color, fragrant aroma not typical Pedada, sweet taste slightly sour and slightly chewy texture and organoleptic assessment results overall hedonic states rather liked. Keywords: Dodol, sticky rice flour and pedada fruit.